Kualitas Produk, Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Pelanggan Di Subway Mall Kelapa Gading - Melda Julia Rita; Hadi Wasino (Human Capital Development, 2023)
The purpose of this study is to analyze and determine product quality, service quality and brand image on customer satisfaction at Subway Mall Kelapa Gading. The research method used in this study is quantitative descriptive. The sample technique used in this study used Purposive Smapping to determine 108 respondents who had made purchases at Subway Mall Kepala Gading. Data analysis method using Structural Equation Model with data processing using Smart-PLS 3.0. Through several tests, including validity tests, reliability tests, and hypothesis tests. The results showed that product quality does not affect customer satisfaction, service quality also does not have a positive effect on customer satisfaction and on the other hand, brand image has a positive effect on customer satisfaction. Although customer satisfaction can also be influenced by several other factors that are not studied.